Programowanie żywieniowe - wpływ odżywiania kobiet w ciąży na zdrowie dziecka = Nutritional programming - the impact of nutrition of pregnant women on the health of their children - Pudło, Hanna; Respondek, Malwina (Journal of Education, Health and Sport, 2016)
Pudło Hanna, Respondek Malwina. Programowanie żywieniowe - wpływ odżywiania kobiet w ciąży na zdrowie dziecka = Nutritional programming - the impact of nutrition of pregnant women on the health of their children. Journal of Education, Health and Sport. 2016;6(7):589-600. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.59761 http://ojs.ukw.edu.pl/index.php/johs/article/view/3733 https://pbn.nauka.gov.pl/sedno-webapp/works/741379 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Programowanie żywieniowe - wpływ odżywiania kobiet w ciąży na zdrowie dziecka Nutritional programming - the impact of nutrition of pregnant women on the health of their children Hanna Pudło1, Malwina Respondek1 1 Katedra Dietetyki, Wydział Zdrowia Publicznego w Bytomiu, Śląski Uniwersytet Medycznego w Katowicach 1 Department of Dietetics, School of Public Health, Medical University of Silesia in Katowice Słowa kluczowe: ciąża, dieta, programowanie żywieniowe, hipoteza Barkera, przewlekłe choroby niezakaźne. Programowanie żywieniowe to istotna zależność między odżywianiem się kobiet w ciąży, a jakością życia dziecka w przyszłości. Nieprawidłowy bilans energetyczny oraz ilość składników odżywczych w całodziennej racji pokarmowej mogą znacząco wpłynąć na rozwój płodu. Długofalowe badania epidemiologiczne potwierdzają występowanie tzw. “krytycznych okresów” w trakcie rozwoju wewnątrzmacicznego, w których żywienie odgrywa znaczącą rolę. David Barker jako pierwszy opisał zjawisko programowania metabolizmu płodu analizując związek między niską masą urodzeniową a występowaniem chorób sercowo-naczyniowych, insulinooporności, otyłości i cukrzycy typu 2 w wieku dorosłym. Aby wytłumaczyć tą zależność powstało kilka hipotez m.in. “oszczędnego fenotypu” (z ang. thrifty phenotype), która tłumaczy wpływ niedożywienia w okresie ciąży na występowanie zaburzeń funkcjonalnych i strukturalnych komórek beta wysp trzustkowych, nefronów oraz kardiomiocytów. Oporność na insulinę i zaburzenia tolerancji glukozy mogą być programowane podczas tzw. “ratowania płodu” (z ang. fetal salvage). Długotrwały niedobór energii i składników odżywczych prowadzi do zmian adaptacyjnych, które mają na celu dostarczenie glukozy do mózgu kosztem innych organów. Niska masa urodzeniowa postnatalnie doprowadza do wzrastania kompensacyjnego w pierwszych dwóch latach życia, co tłumaczy hipoteza „dogonić wzrost” (z ang. catch-up growth). Natomiast niedobór kwasu foliowego zwiększa ryzyko występowania wad cewy nerwowej u dziecka. Dobrze zbilansowana dieta kobiety ciężarnej może zmniejszyć ryzyko rozwoju chorób i poprawić jakość życia dziecka. Wskazane jest opracowanie programów edukacyjnych na temat wpływu diety na rozwijający się płód. Key words: pregnancy, diet, nutritional programming, Barker hypothesis, chronic diseases. Nutritional programming is an important correlation between nutrition of pregnant women and the quality of children`s life in the future. Abnormal energy balance and amount of nutrients in the daily diet can significantly affect on the development of the fetus. Long-term epidemiological research confirm the occurrence of so called "critical periods" during intrauterine growth, in which nutrition has a significant role. David Barker as a first described the phenomenon of fetus’ metabolic programming by analyzing the relationship between low birth weight and the presence of cardiovascular disease, insulin resistance, obesity and diabetes mellitus II in adult life. There are several hypotheses to explain this correlation. One of them is the hypothesis of thrifty phenotype, which explains the impact of malnutrition during pregnancy on the incidence of functional and structural disorders of pancreatic beta cells, cardiomyocytes and nephrons. Insulin resistance and disorders of glucose tolerance can be programmed during "fetal salvage". Long-term deficiency of energy and nutrients leads to adaptive changes that aim to provide glucose to the brain at the expense of other organs. Low birth weight postnatally leads to compensatory growing in the first two years of life, which explains the hypothesis of "catch-up growth". In addition, folic acid deficiency increases the risk of neural tube defects in the child. A well-balanced diet of a pregnant woman can reduce the risk of developing diseases and improve the quality of the child’s life. It is indicated to prepare educational programs about the effects of diet on the developing fetus.